Genetic diversity fair 2018 - Dutt, Som (Indian Horticulture, 2019)
The Mango and Jackfruit Diversity Fair was organised by Dr G Karunakaran, Head, CHES, Hirehalli, and Dr K M Sankaran, Dr B Narayanaswamy, and Dr R Venkattakumar, during 24-26 May 2018, at ICAR-IIHR, Bengaluru. More than 350 mango varieties showing diversity were shown. Jackfruit, a rich source of varied diversity was also exhibited to the visitors.